Perjuangan Menyelamatkan Muka: Strategi-Strategi Tiongkok Dalam Memulihkan Citra Akibat Covid-19 - Shamira Tridarysa Fathia; Mohamad Rosyidin; Muhammad Faizal Alfian (Journal of International Relations Diponegoro, 2022)
The outbreak of COVID-19 has made China's image deteriorate into an unfavourable view. The government cannot waive this problem. Sectors such as but not limited to economics, anti-China sentiment, and the bullied Chinese diaspora has impacted. Therefore, China must have strategies that can restore its image internationally. Based on the background of the problem, the research question is how are China's strategies in restoring its country image due to the COVID-19 pandemic? To answer this question, the author uses the conceptual framework of Diamond and McDonald's Multi-Track Diplomacy. It then argues that China uses the strategies in the Multi-Track Diplomacy operating tracks one (government) and nine (media and communication) to restore its image. This study finds that China carries those strategies in tracks one and nine to recover their image by image building. The type of data used in this research is qualitative and analysed using narrative data analysis methods.